Life as quale - Cazalis, Roland (Pensamiento. Revista de Investigación e Información Filosófica, 2013)
The developments of relational biology during these last thirty years tend to classify autonomous system such as biological, cognitive or social groups among the living systems which they models as such. This present article tries to understand the nature of life by the transition phase which characterizes the passage from the inanimate world to the organic one. Our proposal is that life belongsto the category of qualia. Consequently, qualia are already obvious at least with the simplest forms of the living world. Furthermore, if life, consciousness and language are emergences of complex entities,life as quale is specifically the self of the cellular organism.